Is fibromuscular dysplasia underdiagnosed? A comparison of the prevalence of FMD seen in CORAL trial participants versus a single institution population of renal donor candidates. (October 2014) - Hendricks, Nicholas J; Matsumoto, Alan H; Angle, John F; Baheti, Aparna; Sabri, Saher S; Park, Auh W; Stone, James R; Patrie, James T; Dworkin, Lance; Cooper, Christopher J; Murphy, Timothy P; Cutlip, Donald E
Renal artery fibromuscular dysplasia (FMD) may be underdiagnosed. We evaluated the prevalence of FMD in CORAL (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) renal artery stent trial participants, in which FMD was an exclusion criterion for inclusion. We also evaluated the prevalence of FMD in a relatively healthy population of patients undergoing computed tomographic angiographic (CTA) screening for renal donor evaluation. All renal donor CTAs performed at our institution from January 2003 through November 2011 were retrospectively reviewed for the presence of FMD along with patient sex and age. These results were compared to angiographic core lab (ACL) findings for the CORAL trial. The CORAL ACL database contained 997 patients (mean age 69.3 years; 50% female). Fifty-eight (5.8%) CORAL trial patients (mean age 71.8 years; 75.9% female) demonstrated incidental FMD. The renal donor cohort included 220 patients (mean age 40.5 years; 64.5% female). Five (2.3%) demonstrated FMD (mean age 48.6 years; all female). The odds of FMD in the CORAL cohort were 2.65 times that seen in the renal donor cohort (95% CI: 1.12, 7.57). Inc onclusion, the 5.8% prevalence of renal artery FMD in the CORAL trial population, the presence of which was biased against, suggests underdiagnosis.